Faktor-Faktor Yang Berhubungan Dengan Motivasi Pasien Kanker Menjalani Kemoterapi Di Rumah Sakit X - Banga Allo, Kartika (Jurnal Kesehatan, 2021)
Cancer is a chronic disease that requires a long and complex treatment. One of cancer therapies is chemotherapy, which often causes side effects, so the patients need motivation. The aim of this research is to analyze the factors related to the motivation of cancer patients undergo chemotherapy. This research used cross sectional with descriptive correlation approach. Total sample of 40 cancer patients undergoing chemotherapy, taken by purposive sampling. The data collection tool is a questionnaire. The univariate statistic results showed the majority of respondent's age ? 47 years is 55%, female gender is 100%, good knowledge is 85%, has side effects as much as 100%, chemotherapy cycles ? 4 cycles are 57%, good family support is 85%, good nurse support as much as 90%, strong motivation as much as 77.5%. The Chi-Square statistic results showed that there is a relation between nurse support and motivation of cancer patients undergoing chemotherapy at Hospital X p = 0.000 (p <0.05); There is no significant relation between age and motivation p = 0.258, knowledge with motivation p = 0.884, chemotherapy cycle with motivation p = 0.328, and family support with motivation p = 0.634: (p> 0.05). In conclusion, nurse support is able to increase the motivation of cancer patients undergoing chemotherapy.